Manutenção da qualidade e aumento da longevidade floral de crisântemo cv. White polaris - Flórez-Roncancio, Victor Julio; Castro, Carlos Eduardo Ferreira de; Demattê, Maria Esmeralda Soares Payão [UNESP] (Instituto Agronômico de Campinas, 1996)
0 objetivo do trabalho foi determinar o melhor tratamento pós-colheita para manutenção floral e aumento da longevidade de crisântemo de maço do tipo pompom (Dendranthema grandiflorum (Ramat.) S. Kitamura) cv. White Polaris. Estabeleceu-se como ponto de colheita o momento em que as hastes apresentavam três inflorescências apicais com as pétalas externas em ângulo de 45° em relação à horizontal. Durante o ensaio em laboratório, as hastes, colhidas em estufa de produção comercial, após totalmente imersas em água de torneira, à sombra, durante três horas, foram cortadas sob água na base do caule entre 50 e 60 cm. As hastes foram distribuídas nos diferentes tratamentos de pulsing durante 24 horas, com luz contínua de 1.500 lux, 60 a 90% de umidade relativa do ar e temperatura ambiente de 25 ± 2°C. No primeiro experimento, testou-se a eficiência de 8-hidroxiquinolina (8-HQ) e tiabendazole (TBZ) como germicidas de manutenção da qualidade na solução de pulsing; testaram-se, também, dois reguladores de crescimento, a saber: ácido giberélico (GA3), 6-benzilaminopurina (6-BA) ou a mistura dos dois, com o objetivo de preservar a cor e a turgidez da folhagem. Os melhores resultados foram com 8-HQ (0,69 mol/m³) e GA3 (0,058 mo1/m³). No segundo experimento, avaliaram-se os seguintes inibidores de etileno: tiossulfato de prata (STS), nitrato de prata (AgNO3) e cloreto de cobalto (COC1(2)). A melhor resposta foi obtida com AgNO3 (2,9 e 4,4 mo1/m³).

Cut flowers of spray chrysanthemum (Dendranthema grandiflorum (Ramat.) S. Kitamura) cv. White Polaris were harvested and treated in pulsing solutions. The flowers were harvested in commercial greenhouses and transported to the laboratory where the whole stem and inflorescence were immersed in tap water at darkness, during 3 hours. The flowers were selected for uniformity in terms of development; the stems were trimmed to equal length (50 to 60 cm) and tagged to allow recording morphological changes associated with individual flowers. The flowers were held during 24 hours (pulsing treatment period) at 25 ± 2°C and 60 to 90% of air relative humidity under continuous cool white fluorescent light at 1.5 KLx. At the end of the treatment, the flowers were transferred to distilled water, under daily 10 hours of continuous fluorescent light and at the same laboratory conditions already described. At the first experiment, it was tested the efficiency of 8-hydroxyquinoline (8-HQ) and thiabendazole (TBZ), as germicides, in three concentrations each one. Furthermore, two growth regulators were applied in order to keep the green color and the turgidity of leaves: gibberellic acid (GA3), 6-benzylaminopurine (6-BA) and a mix of them. At the second experiment, in order to extend the vase-life by inhibition of ethylene production, it was tested the effect of silver nitrate (AgNO3), anionic silver thiosulphate complex (STS) and cobalt chloride (CoCl2) into pulsing solutions in three concentrations each one. The results of experiments showed that pulsing treatment with distilled water + 0.52 mol/m³ citric acid + 58.43 mol/m³ sucrose + 0.69 mol/m³ 8-HQ + 2.9 or 4.4 mol/m³ AgNO3, combined with foliar treatment of 0.058 mol/m³ GA3, improved the foliar quality and extended the flower vase life.
Keeping quality and prolonging the postharvest longevity of spray chrysanthemum cv. White polaris
Keywords: Chrysanthemum; Postharvest; germicides; ethylene inhibition; Crisântemo; Pós-colheita; germicidas; inibidores de etileno